The Role of Candida albicans Secreted Polysaccharides in Augmenting Streptococcus mutans Adherence and Mixed Biofilm Formation: In vitro and in vivo Studies - Khoury, Zaid H.; Vila, Taissa; Puthran, Taanya R.; Sultan, Ahmed S.; Montelongo-Jauregui, Daniel; Melo, Mary Anne S.; Jabra-Rizk, Mary Ann (Frontiers in Microbiology, 2020)
The oral cavity is a complex environment harboring diverse microbial species that often co-exist within biofilms formed on oral surfaces. Within a biofilm, inter-species interactions can be synergistic in that the presence of one organism generates a niche for another enhancing colonization. Among these species are the opportunistic fungal pathogen Candida albicans and the bacterial species Streptococcus mutans, the etiologic agents of oral candidiasis and dental caries, respectively. Recent studies have reported enhanced prevalence of C. albicans in children with caries indicating potential clinical implications for this fungal-bacterial interaction. In this study, we aimed to specifically elucidate the role of C. albicans-derived polysaccharide biofilm matrix components in augmenting S. mutans colonization and mixed biofilm formation. Comparative evaluations of single and mixed species biofilms demonstrated significantly enhanced S. mutans retention in mixed biofilms with C. albicans. Further, S. mutans single species biofilms were enhanced upon exogenous supplementation with purified matrix material derived from C. albicans biofilms. Similarly, growth in C. albicans cell-free spent biofilm culture media enhanced S. mutans single species biofilm formation, however, the observed increase in S. mutans biofilms was significantly affected upon enzymatic digestion of polysaccharides in spent media, identifying C. albicans secreted polysaccharides as a key factor in mediating mixed biofilm formation. The enhanced S. mutans biofilms mediated by the various C. albicans effectors was also demonstrated using confocal laser scanning microscopy. Importantly, a clinically-relevant mouse model of oral co-infection was adapted to demonstrate the C. albicans-mediated enhanced S. mutans colonization in a host. Analyses of harvested tissue and scanning electron microscopy demonstrated significantly higher S. mutans retention on teeth and tongues of co-infected mice compared to mice infected only with S. mutans. Collectively, the findings from this study strongly indicate that the secretion of polyssacharides from C. albicans in the oral environment may impact the development of S. mutans biofilms, ultimately increasing dental caries and, therefore, Candida oral colonization should be considered as a factor in evaluating the risk of caries.